Can simple household assistive products enhance the self-care of health and well-being?. Issue 2 (30th March 2023) - Nachiappan, Nitish; Ward, Sophie; Chockalingam, Nachiappan; Chambers, Ruth
Abstract : Purpose: The ageing population is a global phenomenon that is occurring in many countries around the world, including the UK. According to the Office for National Statistics (ONS), the proportion of the UK population aged 65 years and over is projected to increase, reaching 25% by 2045. This increase will have a significant impact on a range of social and economic issues. One of the ways to reduce this impact is to improve self-care. Design/methodology/approach: The availability of simple assistive devices can facilitate physical activity and help complete daily living activities. These devices can also help in the self-management of long-term health and well-being. To encourage self-care, it is essential to create awareness about these assistive products. Simple assistive products such as shoe horns, magnifying glasses or a sphygmomanometer that are readily available to buy from shops were grouped into four boxes or kits. The authors provided these simple devices to 175 community-dwelling older adults in deprived areas and followed them up via a phone survey after 4–6 weeks. Findings: The authors recorded overall positive feedback on individual products and the kit. The results indicate that there was a sense of empowerment and ability by the recipients to take control of their health and well-being and management of their health condition using items contained in the kit provided. Practical implications: The study results show that simple assistive products empower older adults to self-care and can provide a positive impact on their activities of daily living. Originality/value: Previous studies have shown that regular exercise can enhance both physical and mental abilities and reverse certain chronic health issues. Simple household devices can aid in increasing physical activity. This work highlights how these devices enable older adults to take care of themselves, with a focus on capturing their personal perspectives and experiences.